Oil-water separator / Muhammad Zaki Mahussin and Nik Muhammad Hasnan Nik Ibrahim - Mahussin, Muhammad Zaki; Nik Ibrahim, Nik Muhammad Hasnan (2003)
Oil pollution is one of the pollutions that effects environmental such as water resources, living organism, human being and others. Nowadays only big factories have the unit to control pollution while oil spills in small workshops, pump stations and others are mostly neglected. Most of the workshops in Malaysia contribute to oil pollution. We see that the oil flowing through the drain and then direct to the river where it does a lot of damage to living things. The oil pollution actually will effect the flora and fauna and also disturb the ecosystem. Realising this, we will prepare a design of a low scale oil-water separator especially for small workshop such as car or motorcycle workshop. The oil-water separator that we will design is suitable for small workshop. We see that from the size aspect and the price that affordable to all workshops. When the oil-separator unit are installed in workshops, it can reduce the oil discharge into the river and help control the pollution.